Cultural Communications Between China and The Outside World Throughout History - Shen, Fuwei. author. aut Link
XII, 319 p. 3 illus.
Keywords: This book starts from the very beginning of the cultural exchanges between China and the western regions, to the exchanges in modern times, featuring large time span and interdisciplinarity. In addition to elaborate illustrations including precious pictures and sketch maps, a large amount of archaeological data, as well as both Chinese and foreign literature, are employed in the book to provide the readers with a comprehensive, in-depth and systematic introduction of the cultural exchanges between China and the west regions from neolithic age to present China after Reform and Opening Up. The intended readership includes professionals, college students, graduates specializing in Chinese history, philosophy and culture, as well as those interested in oriental civilizations. Shen Fuwei (1935-2021) was a recognized authority in cultural history study. He was a professor at the School of Society, Soochow University, vice president of the World History Academic Society of Jiangsu Province, and member of the Chinese Society for Historians of China’s Foreign Relations and the China Society for Maritime History Studies. His researches focus on Asian culture, cultural exchanges between China and the outside world, modernization and world economy. He wrote Cultural Exchanges Between China and Outside World Throughout History, China and Africa: a History of Foreign Contacts of 2000 years, Cultural Flow Between China and Outside Word Throughout History, China’s Cultural Exchanges with West Asia and Africa. He was also the editor-in-chief of The History of Chinese Civilization. He published over 40 papers throughout his career. He was born in Suzhou, Jiangsu Province, and graduated from Fudan University.